Enhancing Students’ Speaking Skills through the Agree-Disagree Line Games - Risa Anggraini; Anni Holila Pulungan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate the effectiveness of the Agree–Disagree Line Game in improving the speaking skills of first-semester students in an Indonesian EFL classroom, grounded in Long’s Interaction Hypothesis, which emphasizes the role of interaction in language development. The study employed Classroom Action Research consisting of two cycles conducted over eight meetings within one semester and involved 20 first-semester students from the English Department of a private university in Medan. Quantitative data were collected through speaking tests, while qualitative data were obtained from interviews. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed thematically. The quantitative findings indicated a clear improvement in students’ speaking performance, with the mean speaking score increasing from 62 in the pre-test to 80.65 in the final post-test. This improvement was further supported by qualitative findings, which showed that students became more active, confident, and motivated during speaking activities. The results indicate that the Agree–Disagree Line Game can serve as an effective game-based learning strategy and provide practical pedagogical implications for EFL teachers in fostering interactive speaking instruction at the tertiary level.